Raman scattering measurements of phonon anharmonicity in the delafossite CuGa1‐xCrxO2 (0 ≤ x ≤ 1) films. (12th February 2020) - Han, Meijie; Lu, Yonggeng; Liu, Yonghui; Hu, Zhigao; Chen, Guochu; Jiang, Kai; Zhang, Jinzhong; Li, Wenwu
Abstract: Raman spectra of the delafossite CuGa1‐ x Cr x O2 (0 ≤ x ≤ 1) solid solution films have been measured in the temperature range from 80 to 823 K. Raman phonon modes are observed at 224 ( A g ), 328 ( A 2u ), 396 ( E g ), and 757 ( A 1 g ) cm −1 for the CuGaO2 film, and phonon modes of the CuCrO2 film are around 211 ( A g ), 324 ( A 2u ), 458 ( E g ), and 712 ( A 1g ) cm −1, respectively. The A 1g phonon mode has a distinct redshift with increasing Cr composition, which indicates that the interatomic potential becomes weaker between Cu and O atoms. Except Raman modes at the Brillouin zone center, the additional phonon modes in the spectral range of 500−670 cm −1 were observed due to Raman selection rules being relaxed by the crystal defects. With increasing temperature, the A 1g phonon mode undergoes a larger phonon softening but a smaller line broadening relative to that of the E g phonon mode, which indicated the anisotropic behavior for the delafossite CuGa1‐ x Cr x O2 films. The nonlinear temperature dependence of the phonon frequency and linewidth is an indication of nonharmonic lattice dynamics. The Raman shift and the linewidth of the E g and A 1g optical modes as a function of temperature were studied as an experimental evidence of the combined effect of lattice expansion and anharmonic phonon–phonon interaction. And the three‐phonon anharmonic coupling plays the dominant role in the anharmonicity behavior. The phonon anharmonicity behavior of the CuGaO2 and CuCrO2 films is slightly different. The larger Γ 0 is intrinsic for the A 1g mode of the CuGa0.8 Cr0.2 O2 film due to the broadening by the crystalline defects, which perturb the translation symmetry of the harmonic crystal, making the momentum conservation rule for phonon scattering partially relaxed. Abstract : Raman vibration and the phonon anharmonicity of the delafossite CuGa1‐ x Crx O2 (0≤x≤1) films were investigated by temperature‐dependent Raman scattering. With increasing temperature, the A 1g phonon mode under goes a larger phonon softening but a smaller line broadening relative to that of the E g phonon mode, which indicated the anisotropic behaviour for the CuGa1‐ x Crx O2 films. For the CuGa1‐ x Crx O2 films, the three phonon anharmonic coupling play the dominant role in the anharmonicity behavior, though the phonon anharmonicity behavior of the CuGaO2 and CuCrO2 films is slightly different.